2009
DOI: 10.1037/a0017063
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of endogenous opioids to gonadal hormones-induced temporomandibular joint antinociception.

Abstract: The authors have recently demonstrated that the high serum estradiol level during the proestrus phase of the estrous cycle and that the administration of estradiol or progesterone in ovariectomized female and of testosterone in orchiectomized male rats significantly decrease formalin-induced temporomandibular joint (TMJ) nociception. In this study, the authors investigate the contribution of endogenous opioids to this antinociceptive effect of gonadal hormones in the TMJ formalin test. The opioid receptor anta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 46 publications
(85 reference statements)
2
20
0
3
Order By: Relevance
“…Conversely, there are indications that male reproductive hormones may have a protective function in association with pain: animal studies have demonstrated that testosterone reduces formalin-induced temporomandibular joint nociception in rats [12]. This antinociceptive effect is probably mediated by the endogenous opioid system [5,11,12]. This may explain why in our study the prevalence of self-reported variables rose in girls, while falling in boys experiencing puberty.…”
Section: Impact Of Pubertal Development On Tmd Symptomssupporting
confidence: 34%
“…Conversely, there are indications that male reproductive hormones may have a protective function in association with pain: animal studies have demonstrated that testosterone reduces formalin-induced temporomandibular joint nociception in rats [12]. This antinociceptive effect is probably mediated by the endogenous opioid system [5,11,12]. This may explain why in our study the prevalence of self-reported variables rose in girls, while falling in boys experiencing puberty.…”
Section: Impact Of Pubertal Development On Tmd Symptomssupporting
confidence: 34%
“…Investigation of the role of endogenous opioids in antinociceptive action of sex hormones has demonstrated considerable nociception reduction both after administering testosterone to male rats post-inguinal orchiectomy, as well as after estradiol and progesterone administration to female rats post-ovariectomy [21]. Moreover, considerable reduction in formalin-induced temporomandibular joint (TMJ) nociception has been reported in the pro-oestrus cycle phase during which high estradiol levels are maintained [12].…”
Section: Discussionmentioning
confidence: 99%
“…Neste estudo foi encontrada correlação entre a sensibilidade à dor (LDP) e o cortisol salivar, apesar deste não ser considerado um marcador biológico preciso na dor crônica (LAMBERT et al, 2013;JASIM et al, 2014, JO et al, 2016 (JONES et al, 1997;DOEPEL et al, 2009;NILSSON et al, 2010;JASIM et al, 2014;SALAMEH et al, 2015;TOSATO et al, 2015;JO et al, 2016 (FISCHER et al, 2009;VILANOVA et al, 2015).…”
Section: Sensibilidade à Dor (Limiar De Dor à Pressão)unclassified
“…Os homens e as mulheres em fase de menopausa não apresentam flutuações hormonais significativas, portanto apresentam menor predisposição à DTM dolorosa (FISCHER et al, 2009 (TURNER et al, 2011;VILANOVA et al, 2015).…”
Section: Sensibilidade à Dor (Limiar De Dor à Pressão)unclassified